Systematic Literature Review Fungsi dan Tujuan Administrasi Pendidikan di Indonesia - Bambang Firmansyah; Mashuri Mashuri (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2022)
Education has a strategic role in various aspects of human life, nation and state. Therefore, good education needs to be supported by good administration. The implementation of educational administration in Indonesia is one of them supported by the competence of administrative personnel, therefore it is necessary to understand the important role of educational administration in achieving educational goals. This research method is qualitative with library research design. Techniques used to collect and analyze data sources using Systematic Literature Review (SLR) method. The results of the analysis showed that the function of education administration is the planning, then the organization and implementation of the work, which does not escape the supervision, direction, coordination, reporting and planning in budgeting funds in education. While the purpose of education administration in Indonesia, first to raise faith and taqwa to God Almighty, then second is to uphold the morals or behavior, morals and have a personality to improve the spirit of nationality. Education administration has several principles including, flexible, efketivitas and efficiency, has orientation on the goal or goal, continuity and lifelong education. ABSTRAK Pendidikan mempunyai peran strategis di berbagai aspek kehidupan manusia, bangsa dan negara. Pendidikan yang baik perlu ditunjang oleh administrasi yang baik. Pelaksanaan administrasi pendidikan di Indonesia salahsatunya ditunjang oleh kompetensi tenaga administrasi oleh sebab itu diperlukan pemahaman peran penting administrasi pendidikan dalam mencapai tujuan pendidikan. Metode penelitian ini adalah kualitatif dengan desain library research. Teknik yang digunakan untuk mengumpulkan dan menganalisis sumber data dengan metode Systematic Literature Review (SLR). Hasil analisis menunjukan bahwa fungsi dari administrasi pendidikan yaitu adanya perencanaan, selanjutnya pengorganisasian dan pelaksanaan pekerjaan, yang tidak luput dari pengawasan, pengarahan, pengkoordinasian, pelaporan dan perencaaan dalam mengaanggarkan dana dalam pendidikan. Sedangkan tujuan administrasi pendidikan yang ada di Indonesia, Pertama untuk menaikan iman dan taqwa kepada Tuhan Yang Maha Esa, kemudian kedua adalah menjunjung tinggi moral atau perilaku, akhlak dan memiliki kepribadian untuk meningkatkan semangat kebangsaan. Administrasi pendidikan mempunyai beberapa prinsip diantaranya, fleksibel, efketivitas dan efisiensi, memiliki orientasi pada tujuan atau goal, kontinuitas dan pendidikan sepanjang hayat.